Sistem Informasi Akademik Universitas Berbasis SQLPage (International Forum of Researchers and Lecturers, 2025)
The academic information system is a crucial element in managing academic data in higher education institutions. Universities require an efficient information system to manage student data, faculty, courses, and other academic administration. This study develops an SQLPage-based information system to provide a lightweight and user-friendly web-based solution. SQLPage enables the creation of web applications directly from a MySQL database without requiring complex programming. The research results show that this system can improve the efficiency of academic data management and ease of access to information for users